The Relationship Between The Need for Learning and Members Participation in the Women Farmens’ grop Program in Pesisir Selatan District - Vilma Putri, Ulfa; Setiawati, Setiawati (Universitas Negeri Padang, 2024)
This research was motivated by the low participation of the Lakuak light gurami farming group of women in Pesisir Selatan Regency, this is thought to be related to their learning needs. This research aims to (1) Describe the learning needs of participants in the women's farmer group program in Pesisir Selatan Regency (2) Describe the participation of members in the women's farmer group program in Pesisir Selatan Regency (3) To see the relationship between learning needs and member participation in the women's group program farmers in Pesisir Selatan Regency. This research uses a quantitative approach with a correlational type. The population of this study were members of the light gourami farming group of women in Lakuak Nagara Kambang Barat, totaling 20 people. The sampling technique is because the population is less than 100, so all of them are taken, so this research is a population. The data collection technique uses a questionnaire and data collection tools in the form of a list of statements. Data analysis techniques use percentages and rank order. The results of this research show that (1) the learning needs of participants in the women's farmer group program in Pesisir Selatan Regency are categorized as low. (2) Member participation in the women's farmer group program in Pesisir Selatan Regency is categorized as low. (3) The results of data management show that there is a significant relationship between learning needs and participation in the women's farmer group program in Pesisir Selatan Regency. This is proven and it is found that the rcount results are greater than the rtable